Medosebna usmerjenost, subjektivno psihološko blagostanje in akademski dosežki študentov - Čotar Konrad, Sonja (Sodobna pedagogika, 2020)
The aim of the study presented in the paper was to determine the correlation between students' interpresonal, attitudes toward mutual cooperation and study assistance, the subjective psychological well-being of students and academic achievements. The study included 219 students of University of Primorska. The results show that students perceive relatively high interpersonal orientation, cooperative learning and mutual support in studies as highly important and significantly correlated. The results also indicate that students with higher academic achievement compared to students with lower academic achievement report a higher level of tendency to participate and self-discloser in group activities. The results point to the importance of the higher education teacher's role in promoting peer connection between students in terms of supporting their developmental tasks. We also highlight the importance of including group work in higher education teaching in terms of responding to students' psychological needs and enabling higher level of study efficiency. As a result, we strongly suggest the need to introduce socio-emotional education at the higher education level.
Keywords: akademski dosežki; medosebni odnosi; psihološko blagostanje; skupinsko delo; sodelovanje; študenti; visokošolski študij